Interspecies Hybridisation and Genome Chimerisation in Saccharomyces: Combining of Gene Pools of Species and Its Biotechnological Perspectives - Sipiczki, Matthias (Frontiers in Microbiology, 2018)
Over the last one and a half decade, interspecies hybridisation has gained continuously increasing attention as a breeding technique suitable for transferring of genetic information between Saccharomyces species and mixing of their gene pools without genetic engineering. The hybrids frequently show positive transgressive phenotypes. Segregation of the hybrid genome results in mosaic (chimeric) strains that can outperform both the parents and the hybrids or exhibit novel positive phenotypic properties. Mitotic segregation can take place during the vegetative propagation of the sterile allodiploid hybrid cells. Meiotic segregation becomes possible after genome duplication (tetraploidisation) if it is followed by break-down of sterility. The allotetraploid cells are seemingly fertile because they form viable spores. But because of the autodiploidisation of the meiosis, sterile allodiploid spores are produced and thus the hybrid genome does not segregate (the second sterility barrier). However, malsegregation of MAT-carrying chromosomes in one of the subgenomes during allotetraploid meiosis (loss of MAT heterozygosity) results in fertile alloaneuploid spores. The breakdown of (the second) sterility barrier is followed by the loss of additional chromosomes in rapid succession and recombination between the subgenomes. The process (genome autoreduction in meiosis or GARMe) chimerises the genome and generates strains with chimeric (mosaic) genomes composed of various combinations of the genes of the parental strains. Since one of the subgenomes is preferentially reduced, the outcome is usually a strain having an (almost) complete genome from one parent and only a few genes or mosaics from the genome of the other parent. The fertility of the spores produced during GARMe provides possibilities also for introgressive backcrossing with one or the other parental strain, but genome chimerisation and gene transfer through series of backcrosses always with the same parent is likely to be less efficient than through meiotic or mitotic genome autoreduction. Hybridisation and the evolution of the hybrid genome (resizing and chimerisation) have been exploited in the improvement of industrial strains and applied to the breeding of new strains for specific purposes. Lists of successful projects are shown and certain major trends are discussed.